Reduced skin permeation and penetration of clobetasol propionate when Dermovate cream is applied at short time intervals with emollients - M. T. Beebeejaun; M. B. Brown; V. Hutter; L. Kravitz; W. J. McAuley (Wiley, 2023)
Abstract Background Dermovate cream containing 0.05% clobetasol propionate is a very potent topical corticosteroid (TCS) used in the treatment of severe inflammatory dermatoses. Regular emollient therapy should continue alongside clobetasol propionate treatment, however, the impact on drug delivery to the skin when both products are applied at similar times is unknown. Objectives To assess whether application of emollients at similar times to Dermovate cream alter the delivery of clobetasol propionate to the skin. Methods This study was conducted using ex vivo human skin mounted in Franz cells. Dermovate cream was applied before or after three different emollients, Hydromol Intensive cream, Doublebase gel, and Diprobase ointment at 5‐ or 30‐min intervals. Drug delivery to the skin was assessed up to 24 h using high‐performance liquid chromatography. Results Significantly reduced clobetasol propionate delivery to the skin was observed when Dermovate cream was applied either before or after the three different emollients, compared to the application of Dermovate cream alone. The data suggest in situ formation of a mixed Dermovate cream and emollient layer which reduces clobetasol propionate delivery relative to the original product. Applying Dermovate cream after any emollient generally resulted in larger reductions in drug delivery to the skin, compared to when the steroid was applied first. This was attributed to the emollients forming an additional barrier to drug delivery at the skin‐formulation interface. Conclusions These findings indicate that applying Dermovate cream at similar times as emollients can significantly reduce drug delivery to the skin and that separating the application of the two products by intervals of up to 30 min is not sufficient to mitigate this effect.